PCR-based markers for genetic mapping in Neurospora crassa. - Moshi Kotierk; Myron L. Smith (Fungal Genetics Reports, 2004)
Eighteen PCR-based markers are described for use in mapping mutations in Oak Ridge background strains of Neurospora crassa. These markers are located on each of the seven linkage groups and in the mitochondrial genome to enable course-scale linkage mapping. Following mapping to a linkage group, additional markers can be developed in the co-segregating region for fine-scale mapping of mutations. As with the N. crassa RFLP map (Metzenberg and Grotelueschen, 1993; Nelson and Perkins, 2000), the addition of PCR-based markers by members of the Neurospora community will enhance this marker set for mapping purposes.